2007
DOI: 10.1113/expphysiol.2007.037150
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sample entropy statistic as a measure of complexity and regularity of renal sympathetic nerve activity in the rat

Abstract: In this study, we employed both power spectral analysis and cross-sample entropy measurement to assess the relationship between two time series, arterial blood pressure (ABP) and renal sympathetic nerve activity (RSNA), during a mild haemorrhage in anaesthetized Wistar rats. Removal of 1 ml of venous blood decreased BP (by 7.1 ± 0.7 mmHg) and increased RSNA (by 25.9 ± 2.4%). During these changes, the power in the RSNA signal at heart rate frequency was reduced but coherence between the spectra at heart rate fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…On the other hand, the results suggest that compared with linear CC, CF, and nonlinear MI, the three entropy-based measurements-XCE, XSampEn, and XFuzzyEn-perform better in measuring the electromechanical coupling. This is in accordance with many previous studies which have shown that entropy-based methods generally are better capable for measuring nonlinear features of cardiovascular system [10,26,32,53]. Furthermore, XFuzzyEn performed best which supports our previous study that the refined fuzzy membership function is capable to improve the stability and distinguishability of traditional entropy measures [10].…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, the results suggest that compared with linear CC, CF, and nonlinear MI, the three entropy-based measurements-XCE, XSampEn, and XFuzzyEn-perform better in measuring the electromechanical coupling. This is in accordance with many previous studies which have shown that entropy-based methods generally are better capable for measuring nonlinear features of cardiovascular system [10,26,32,53]. Furthermore, XFuzzyEn performed best which supports our previous study that the refined fuzzy membership function is capable to improve the stability and distinguishability of traditional entropy measures [10].…”
Section: Discussionsupporting
confidence: 80%
“…Pattern synchronization has been proposed in the literature as means to characterize the probability of finding similar dynamics between biomedical signals. For example, cross-entropy measures have been applied to heart rate variability (HRV; Porta et al 2007a, b) and also to neural signals (Papadelis et al 2007;Zhang et al 2007;Xie et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…34 Entropy-based measures have been widely used for the analysis of physiological time series to explore the complexity between two time-series. 35,36 C-SampEn measures the relative regularity of two signals, with lower C-SampEn values denoting greater conditional regularity or synchronicity, whereas higher values implicate that the given signals are less predictable (or more complex). While C-SampEn may be intuitively understood as the opposite of temporal correlation, it does not assume that signals are temporally stationary processes, but provides an alternative and complementary measure to assess the nonlinear statistics of PRV.…”
Section: Cross-sample Entropymentioning
confidence: 99%